2017
DOI: 10.1371/journal.pone.0188354
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of clinical pharmacy services in county hospitals in China

Abstract: BackgroundClinical pharmacy is not only a medical science but also an elaborate public health care system firmly related to its subsystems of education, training, qualification authentication, scientific research, management, and human resources. China is a developing country with a tremendous need for improvements in the public health system, including the clinical pharmacy service system.ObjectivesThe aim of this research was to evaluate the infrastructure and personnel qualities of clinical pharmacy service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The median number of CPs in HCMC [2 (Q1-Q3: 1-4)] was lower than the average number of CPs in Hanoi [2.2 (SD: 1.1)] 10 , whilst in China, a clinical pharmacy team in county hospitals requires more than three CPs. 10,22 Considering FTE, the present median was extremely low, at only 0.4 (Q1-Q3: 1-2) compared to 0.77 FTE CP per hospital in Hanoi. 10 One study of Bond et al reported that a hospital needs averagely 10.7 or 3.2 FTEs CP to cover all or five-core clinical pharmacy activities, respectively; while a requirement of 2-4 FTEs per hospital for these activities was noted in another study (Saudi Arabia).…”
Section: Full-time Equivalentmentioning
confidence: 54%
See 3 more Smart Citations
“…The median number of CPs in HCMC [2 (Q1-Q3: 1-4)] was lower than the average number of CPs in Hanoi [2.2 (SD: 1.1)] 10 , whilst in China, a clinical pharmacy team in county hospitals requires more than three CPs. 10,22 Considering FTE, the present median was extremely low, at only 0.4 (Q1-Q3: 1-2) compared to 0.77 FTE CP per hospital in Hanoi. 10 One study of Bond et al reported that a hospital needs averagely 10.7 or 3.2 FTEs CP to cover all or five-core clinical pharmacy activities, respectively; while a requirement of 2-4 FTEs per hospital for these activities was noted in another study (Saudi Arabia).…”
Section: Full-time Equivalentmentioning
confidence: 54%
“…10 On the other hand, the finding about years of experience was quite identical with China, where the median work seniority of CPs was 4 (Q1-Q3: 2-5). 22 Likewise, in Saudi Arabia, over 95% of surveyed CPs had no more than 1 year of experience in this field. 24 As a whole, the low working seniority of CPs might accord with the fact that the first official Circular of clinical pharmacy was just issued in December 3, 2012…”
Section: Work Senioritymentioning
confidence: 99%
See 2 more Smart Citations
“…The PC system in China is still in an early stage of development, and its quality is unsatisfactory in comparison to that in developed countries [18][19][20][21][22][23][24][25] . With various limitations, Chinese government is exploring approaches for improving the quality of PC [26][27][28][29] .Studies in China have indicated a certain extent of misunderstanding of PC by its providers, such as the concepts that taking the dispensing as the core of PC or the goal of PC is only to solve the drug-related problems raised by the clinicians, and reluctance of performing PC among some providers due to barriers like lacking support from hospital administrators or clinicians [30,31] , which may impair the quality practice of PC.…”
Section: Introductionmentioning
confidence: 99%